'Espaço vital' projetos geopolíticos de Hitler para o território europeu da União Soviética - Schneider, Samuel Celuppi (2016)
The main objective of this dissertation is the analysis of the Soviet Union‘s invasion by nazi Germany in June, 1941, under a geopolitical point of view. Based in Hitler‘s figure, it analyzes his project of turning european Russia‘s territory into german ―living space‖, that is, a huge colony of settlement and economic exploitation. Considering the participation of many nazi leaders, which were crucial in the complex totalitarian german regime, and considering an intellectual and political reality preceding Nazi Party, this work examines the conquest of Soviet Union in the context of nazi expansionist ideology. Subsequently, it analyzes specifically the plans developed during World War II, specially in 1941-43: plans of economic exploitation, german settlement, military domination, landscape modernization and continental hegemony. Finally, it examines the historical inspirations behind nazi expansionism, that is, historical processes defined as models to the conquest of Eastern Europe, for example: german Middle Ages, english imperialism in India, and the formation of the United States. With this purpose, it demonstrate that the taking of Soviet Union represented, since the 20‘s, the main objective of external nazi politics formulated by Hitler, with the geopolitic factor standing out under the military and ideological factors. To identify Hitler's plans, it analyzed here documents such as speeches and meeting records, usually inaccessible to the public at the time, where the dictator used to expose to his private circle what he would do if Germany won World War II. The Nazi imperial planning also included other regions of Europe conquered and inhabited by Slavs, especially Poland, beyond the former Czechoslovakia, but it was in the Soviet space, dominated by the Bolshevik communism, that the Nazi‘s racism appeared with all intensity. It was Eastern Europe, particularly the areas inhabited by Ukrainians and Russians, that Hitler regarded as the key to the German continental hegemony and eventually to global power politics.